Daughter of the pirate king - Levenseller, Tricia (New York : Feiwel and Friends, 2017)
"When her father, the ruthless pirate king, discovers that a legendary treasure map can be found on an enemy ship, his daughter Alosa knows that there's only one pirate for the job herself. Leaving behind her beloved ship and crew, Alosa deliberately facilitates her own kidnapping to ensure her welcome on the ship"--
Keywords: Pirates -- Fiction; Princesses -- Fiction; Love -- Fiction